Self-Regulation Skills Training and Secondary School Students’ Self-Concept in Written Composition in Jos North, Nigeria - Ajaero, Lilian Ekpere; Haggai, Mary Plangnan (NIU Journal of Humanities, 2020)
This study focused on the effects of self-regulation skills training on secondary school students’ self-concept in written composition in Jos metropolis, Nigeria. The population of the study consists of all the 4240 government senior secondary class two (SS2) students in Jos North Local government area of Plateau State out of which a sample of 100 was selected for the study. Three research questions and three hypotheses were formulated and tested at 0.05 level of significance. The study employed the use of quasi – experimental research design specifically, the non-randomized pre-test-post-test control group design. While a simple random sampling technique was used for selecting 2 schools out of the 20 and 100 students selected for the study.  An instrument ‘self – concept rating scale’ (SCRS) designed to assess various components of self – concept was used as instrument for data collection.  The study used mean rating, standard deviation, and t- test for related sample as techniques for data analysis with 2.50 and 0.05 as the criterion mean and level of significance respectively. Thus, the results of the analysis revealed that students’ self- concept towards written composition improved significantly after exposure to self-regulation training. The analysis of research hypotheses further showed that there is no significant difference in the self-concept of males and females. And there is no significant difference between the control and experimental groups’ perception of their self-concept. This results shows that self-concept depends on the individual. Keywords: Self-Regulation, Skill-Training, Secondary School, Self-Concept, Written Composition